Uses of mobile apps during the covid-19 pandemic: the Portuguese case - Gomes, Natália (2022)
The social isolation caused by the Covid-19 pandemic was a challenge to the ongoing digitisation of societies. The massive use of the Internet and mobile applications has (re)configured social practices, relationships, and labour routines in unprecedented ways. Facing the challenges brought by social isolation, the uses of mobile apps have also changed during this period. Therefore, it is essential to understand how they dialogue with personal, social and civic intervention contexts. Research on mobile applications has mostly taken the theory of uses and gratifications or the approach to risks and opportunities. Specifically, regarding the Covid-19 pandemic, most of the research performed during this period has focused on contact tracing apps and privacy concerns. Considering the lack of in-depth research on the individual, social and civic implications of the uses of mobile applications in Portugal during the period of social isolation, we present an exploratory study to contribute to understanding a). the role of these digital platforms in citizens’ daily lives, and b). the perceptions of people regarding their use of mobile apps. The empirical research, conducted during the first state of emergency the government declared, was operationalised through a quantitative-extensive methodological strategy using an online questionnaire survey. Sampling was non-probabilistic collected through the snowball process (N = 220). Data were analysed using descriptive and inferential (bivariate) statistical analysis. The study indicates that the use of mobile apps became more frequent during social isolation. The results show how contacting family and/or friends through mobile applications and consulting the news media to learn more about the situation have become frequent activities. Regarding the perceptions of usage, results suggest that some patterns are considered a waste of time. The study results contribute to a deeper understanding of the importance of mobile apps in everyday life during social lockdowns. The results also discuss how mobile apps are used in the reconfiguration of social practices, particularly regarding communication with family and friends, as sources for news and to perform leisure activities.